Growth regulators on fruit set and quality of parthenocarpic fruit in atemoya ’Gefner’ - Pereira, Marlon Cristian Toledo; Crane, Jonathan Henry; Nietsche, Silvia; Montas, Wanda; Santos, Márcio Adriano (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the effects of plant growth regulators on the effective fruit set and quality of atemoya ’Gefner’ parthenocarpic fruit. The experiment was carried out in an orchard of atemoya ’Gefner’ in Homestead, Florida, USA. A randomized complete block design was carried out with four treatments, five replicates, and six flowers per plot. Treatments were composed of: T1, 450 mg L‑1 naphthaleneacetic acid and 1,000 mg L‑1 gibberelic acid; T2, 100 mg L‑1 promalin and 1,000 mg L‑1 gibberelic acid; T3, 1,000 mg L‑1 gibberelic acid; and T4, artificial pollination (control). Effective fruit set, and fruit growth and quality were evaluated. The application of naphthaleneacetic and gibberelic acids on flowers of atemoya ’Gefner’ provided high fruit set, similar to that of artificial pollination. Gibberelic acid application, associated or not with naphthaleneacetic acid or promalin, results in later and smaller atemoya ’Gefner’ fruit than those obtained by artificial pollination, but with good proportion of pulp, excellent soluble solids content and, mainly seedless fruit (parthenocarpic fruit).